Jiving and Utilizing Gamification Activities in Science (JUGAS): An Intervention in Improving Grade 11 Students’ Conceptual Understanding - Jugas, Ralph Jade M. (East Asian Journal of Multidisciplinary Research, 2024)
This action research explores the effectiveness of Project JUGAS in enhancing Grade 11 HUMSS students' understanding of Earth and Life Science. Using an explanatory sequential design, the study assessed pretest and posttest scores of students engaged in gamification activities—cabbage relay, geologic crossword puzzles, science mystery stations, and impromptu speech spinners—over four weeks. Results show a significant improvement in mean scores (p=0.00***) with a large effect size (d=0.92). Qualitative analysis identified six key themes: fun and interactive, engaging and motivating, challenging, collaborative, mastery of learning, and progression with rewards. The joint display confirmed that these qualitative themes support the quantitative data, demonstrating Project JUGAS's effectiveness as a pedagogical strategy.